Results from an IFCC global survey on laboratory practices for the analysis of circulating tumor DNA - Linder, Mark W.; Huggett, Jim F.; Baluchova, Katarina; Capoluongo, Ettore D.; Payne, Deborah A.; Salinas, Aldo Vacaflores; Haselmann, Verena; Ashavaid, Tester; Pan, Shiyang; Ahmad-Nejad, Parviz (Clinica chimica acta, 2023)
Background - The clinical validity of ctDNA analysis as a diagnostic, prognostic and predictive biomarker has been demonstrated in many studies. The rapid spread of tests for the analysis of ctDNA raises questions regarding their standardization and quality assurance. The aim of this study was to provide a global overview of the test methods, laboratory procedures and quality assessment practices using ctDNA diagnostics. - Methods - The Molecular Diagnostics Committee of the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC C-MD) conducted a survey among international laboratories performing ctDNA analysis. Questions on analytical techniques, test parameters, quality assurance and the reporting of findings were included. - Results - A total of 58 laboratories participated in the survey. The majority of the participating laboratories (87.7 %) performed testing for patient care. Most laboratories conducted their assays for lung cancer (71.9 %), followed by colorectal (52.6 %) and breast (40.4 %) cancer, and 55.4 % of the labs used ctDNA analysis for follow-up/monitoring of treatment-resistant alterations. The most frequent gene analysed was EGFR (75.8 %), followed by KRAS (65.5 %) and BRAF (56.9 %). Participation in external quality assessment programs was reported by only 45.6 % of laboratories. - Conclusions - The survey indicates that molecular diagnostic methods for the analysis of ctDNA are not standardized across countries and laboratories. Furthermore, it reveals a number of differences regarding sample preparation, processing and reporting test results. Our findings indicate that ctDNA testing is being conducted without sufficient attention to analytical performance between laboratories and highlights the need for standarisation of ctDNA analysis and reporting in patient care.